Virtual Reality (VR) Method to Improve Sense of Place for Interior Design Studio Students - Akhmadi Akhmadi; Athifa Sri Ismiranti; Ahmad Nur Sheha (Journal of ICT Research and Applications, 2024)
Virtual reality (VR) technology has emerged in response to recent developments in the 3-dimensional (3D) world. VR enables people to engage in various metaverse world experiences in a more immersive way. Immersive learning is a learning method that uses 3D digital technology to facilitate the learning process by visualization in the classroom. This research used a case study of the Interior Design II studio course taken by level-2 students of the Department of Interior Design, School of Creative Industries, Telkom University, Indonesia. The Interior Design II course requires students to design the interior of a residence with a minimum area of 100 m2. The method of paired sample test analysis was used to assess student’s preferences for pre-test and post-test statements from the VR intervention method in assessing student’s sense of place in the final design of the course. The results showed significant differences in student preferences during the pre-test (481.3% and 790.6%), which increased during the post-test (641.7% and 801%). The paired sample t-test analysis results also showed a Sig (2-tailed) number of 0.000 < 0.05, so there is a significant relationship between the pre-test and post-test intervention.